Golden Notes for Preventive and Social Medicine-II - Sharma, Gopal Ashish; Rattan, Saurabh; Barwal, Vijay (International Journal Of Community Medicine And Public Health, 2021)
A marvellous effort for the learners of community medicine by young authors Dr. Parimal Patel and Dr. Khushbu Makadia of the book, “Golden notes for preventive and social medicine (PSM) 2nd edition”. This is another significant publication amongst the fraternity of community medicine from the reputed publication house of Jaypee after the official release of IAPSM textbook 1st and 2nd edition.